Tom Sawyer [videorecording (DVD)] - Taylor, Don, 1920-1998; Whitaker, Johnny; Holm, Celeste, 1917-2012; Oates, Warren, 1928-1982 (MGM DVD, 2005)
Mark Twain's boy hero enters a cave with Huck and Becky to save Muff Potter, witness to murder.